Adipose tissue dysfunction as a central mechanism leading to dysmetabolic obesity triggered by chronic exposure to p,p'-DDE - Pestana, Diogo (2017)
The authors thank Giles Yeo (University of Cambridge, Metabolic Research Laboratories, MRC Metabolic Diseases Unit, Cambridge, United Kingdom) for the excellent mentoring support regarding the microarray data analysis and functional profiling. The excellent contribution of the technicians from the Department of Clinical Pathology (Hospital S. Joao, Porto, Portugal) with the determination of biochemical markers is also gratefully acknowledged. This article was supported by ERDF (European Regional Development Fund) through the operation POCI-01-0145-FEDER-007746 funded by the Programa Operacional Competitividade e Internacionalizacao - COMPETE2020 and by National Funds through FCT - Fundacao para a Ciencia e a Tecnologia within CINTESIS, R&D Unit (reference UID/IC/4255/2013); PEst-OE/SAU/UI0038/2011; SFRH/BPD/109158/2015; SFRH/BD/46640/2008, SFRH/BD/64691/2009, SFRH/BD/78367/2011, SFRH/BD/93073/2013, SFRH/BPD/109153/2015, SFRH/BD/47200/2008, SFRH/BPD/75294/2010; and SFRH/BPD/40110/2007. Editor